The impact of improved auditor independence on audit market concentration in China - DeFond, Mark L; Wong, T.J; Li, Shuhua (Journal of Accounting and Economics, 1999)
In an attempt to increase credibility in its capital markets, China recently adopted new auditing standards. Consistent with increased auditor independence, we find that the frequency of modified opinions increases nine-fold subsequent to the adoption of the new standards. However, the increase in modified reports is followed by a decline in audit market share among large auditors – those with the greatest propensity to issue modified reports. We conjecture that this `flight from audit quality’ results from lack of incentives to demand independent auditors. Our findings suggest that government regulation alone is insufficient to create financial markets that foster auditor independence.